Inklusi Keuangan dan Efektifitas Kebijakan Moneter : Studi Kasus Negara Indonesia dan Malaysia - Badrany, Muhammad Taqy; Herlina, Deswita (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2024)
Financial inclusion, defined as access and use of formal financial products and services by individuals and companies, has become a major focus in Indonesia and Malaysia in recent years. Authorities in both countries have implemented various policies and programs to increase financial inclusion, hoping to provide economic benefits, namely reducing inflation. The aim of this research is to analyze the influence of financial inclusion, exchange rates, interest rates, broad money, and GDP on inflation in Indonesia and Malaysia. The data used in this research is secondary data ranging from the period 2013Q1 to 2022Q4. The analytical method used in this research is the Vector Error Correction Model (VECM). The conclusion of this research states that the financial inclusion variable has a negative influence on inflation in Indonesia with a VD contribution at the end of the period of 29.37%, while in Malaysia Financial Inclusion has a positive influence on inflation with a VD contribution at the end of the period of 11.22% . The exchange rate negatively influences inflation in Indonesia and Malaysia with VD contributions at the end of the period of 1.28% and 3.87% respectively. Interest rates have a negative influence on inflation in Indonesia with a VD contribution at the end of the period of 1.71%, while in Malaysia interest rates have a positive influence on inflation with a VD contribution at the end of the period of 13.19%. Broad Money positively influences inflation in Indonesia and Malaysia with VD contributions at the end of the period of 2.27% and 2.57% respectively. GDP has a positive influence on inflation in Indonesia with a VD contribution at the end of the period of 22.01%, while in Malaysia GDP has a negative influence on inflation with a VD contribution at the end of the period of 45.39%.